Transatlantic [large type] : a novel - McCann, Colum, 1965- (Thorndike Press, 2013)
Newfoundland, 1919: Two aviators set course for Ireland as they attempt the first nonstop transatlantic flight in a modified bomber. Dublin 1845-846: On an international lecture tour, Frederick Douglass finds the Irish people sympathetic to the abolitionist cause. New York, 1998: Senator George Mitchell departs for Belfast to shepherd Northern Ireland's volatile peace talks. These three iconic crossings are connected by a series of remarkable women.